PENGARUH PEMAHAMAN AKUNTANSI DAN KETENTUAN PERPAJAKAN SERTA TRANSPARANSI DALAM PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI USAHAWAN PADA UKM DI YOGYAKARTA - Sumianto Sumianto; Ch Heni Kurniawan (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2015)
This study aims to determine the efect of understanding of accounting and tax provisions and the tax transparency on tax compliance. This research was conducted on individual taxpayers SMEs in Yogyakarta. This study used a survey approach as collecting data method. The sample in this study was taken using purposive sampling method. Subjects in this study are individual taxpayers, particularly SMEs in Yogyakarta. Multiple regressions with Likert scale measurement were used as the analysis tools. One hundred respondents individual taxpayers entrepreneurs, especially SMEs in Yogyakarta were used as the respondents and the fnding of this study is that the understanding of the accounting and tax provisions comprehension positive efect on tax compliance. Researchers also found that transparency does not afect the taxpayer compliance.Key Words : Accounting Comprehension , Tax Policy, Transparency, Compliance